2005
DOI: 10.1097/01.mib.0000161917.97136.e2
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Local Cytokine Production in Quiescent Ulcerative Colitis and Its Relationship to Future Relapse: A Prospective Pilot Study

Abstract: Rectal mucosal IL-8 measurement might be an additional objective diagnostic tool that can predict relapse in patients with quiescent UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…The production of inflammatory cytokines is markedly activated by bacterial attachment, and epithelial cells are one major source of these cytokines; therefore, this difference in the pattern of cytokine elevation according to the intestinal segment used for neobladder creation may reflect specific interaction between microbial ligands and host receptor in each organ [23]. Furthermore, the present findings are similar to those observed in inflammatory bowel disease [24][25][26][27]; that is, increased expressions of IL-6 and IL-8 were detected in mucosal biopsy specimens from patients with Crohn's disease and ulcerative colitis, respectively. These findings indicate the distinct participation of each cytokine in the pathogenesis of chronic asymptomatic bacteriuria in ileal and sigmoid neobladders.…”
Section: Discussionsupporting
confidence: 73%
“…The production of inflammatory cytokines is markedly activated by bacterial attachment, and epithelial cells are one major source of these cytokines; therefore, this difference in the pattern of cytokine elevation according to the intestinal segment used for neobladder creation may reflect specific interaction between microbial ligands and host receptor in each organ [23]. Furthermore, the present findings are similar to those observed in inflammatory bowel disease [24][25][26][27]; that is, increased expressions of IL-6 and IL-8 were detected in mucosal biopsy specimens from patients with Crohn's disease and ulcerative colitis, respectively. These findings indicate the distinct participation of each cytokine in the pathogenesis of chronic asymptomatic bacteriuria in ileal and sigmoid neobladders.…”
Section: Discussionsupporting
confidence: 73%
“…Our previous investigation [33][34][35] indicated that a cytokine assay can detect an ongoing escalating inflammation in the mucosa of patients with CD and ulcerative colitis, and that a cytokine assay could be an objective method to assess the degree of background mucosal inflammation. In line with this thinking, in this study ileocolonoscopy was regularly performed and multiple biopsies were obtained from both the terminal ileum and large bowel for cytokine assay.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8, an important inflammatory mediator, has an important role in the activation and recruitment of neutrophils to the inflamed tissues [10][11][12]. Many studies have reported that Partition-bran moxibustion 15 23 10 The differences between the two groups was significant (P \ 0.05), clinical therapeutic effect in partition-herb moxibustion is significantly better than those in partition-bran moxibustion the mucosal IL-8 productions were elevated in active UC patients, and large numbers of neutrophils were found in crypt abscesses [11,[13][14][15]. In UC, mucosal concentration of IL-8 in the inflamed site have been reported to correlate with disease severity [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…IL-8, an important inflammatory mediator, has an important role in the activation and recruitment of neutrophils to the inflamed tissues [10][11][12]. Many studies have reported that the mucosal IL-8 productions were elevated in active UC patients, and large numbers of neutrophils were found in crypt abscesses [11,[13][14][15]. In addition, intercellular adhesion molecule-1 (ICAM-1) may play an important role in the occurrence and development of inflammation by inducing the rolling and adherence of neutrophilic granulocyte and monocyte on the endothelial cell [16,17].…”
Section: Introductionmentioning
confidence: 99%